AYURVEDA AS A CO-THERAPY IN THE MANAGEMENT OF OLIGOASTROCYTOMA: A CASE STUDY - Virendra Singh Hada; Harish Bhakuni; Radhika.S.Pukale (International Journal of Ayurveda and Pharma Research, 2020)
Anaplastic astrocytoma (AA) is a diffusely infiltrating malignant, astrocytic, primary brain tumour with a peak incidence between 40 to 50 years of age is a leading cause of cancer death. Though cancer chemotherapy is highly effective in many cancers, but side-effects of chemotherapy are severe in many patients like myelosuppression, anorexia, weight loss, mucositis, fatigue, nausea, vomiting and diarrhoea. It appears that side effects of chemotherapy are manifestations of aggravated Tridosha as Raktadushti (vitiated blood). Therefore, present case study was undertaken to find effectiveness of Ayurvedic medication as an adjuvant or co-therapy in the management of oligoastrocytoma as well as in minimizing the side effect of chemo-radiotherapy. A female patient of age 40 years with brain cancer (clinically diagnosed case of anaplastic oligoastrocytoma grade 3rd) undergoing oral chemotherapy by irnocam 150 mg, avastin 400mg for 6 cycle and radiotherapy was taken. Patient was given classical Ayurvedic formulation of Rasa sindur 50mg+ Abhrakbhasma 250mg+ Vachachurna 500mg+ Panchamritalauha guggulu 250mg BD with honey, Shatavarighrita 5gm BD with milk, Jyotishmatitaila 5 drops BD with Bataasha and cap SNEC30 (liquid curcumin capsules). After the completion of 6th cycle there were very encouraging results observed with negligible side effects, improvement in all chief complaints, general health condition and quality of life of the patient. Ayurvedic medication appears to have significant effect on reducing side effect of chemo-radiotherapy and improving quality of life in the patient of brain cancer (oligoastrocytoma).